2018
DOI: 10.1016/j.jecp.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Infant perception of sex differences in biological motion displays

Abstract: We examined mechanisms underlying infants' ability to categorize human biological motion stimuli from sex-typed walk motions, focusing on how visual attention to dynamic information in point-light displays (PLDs) contributes to infants' social category formation. We tested for categorization of PLDs produced by women and men by habituating infants to a series of female or male walk motions and then recording posthabituation preferences for new PLDs from the familiar or novel category (Experiment 1). We also te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 84 publications
3
11
0
Order By: Relevance
“…This outcome appears to dovetail with recent reports indicating that females and males tend to use different types of information during BM processing and gender recognition in point-light displays: females rely on form and motion cues together, whereas males use motion cues solely (Hiris et al, 2018). This is also in line with recent findings on gender recognition in human infants aged 4-18 months: in a habituation paradigm, boys more easily differentiate the gender of a pointlight walker, presumably possessing higher sensitivity to motion parameters (Murray et al, 2018;Tsang et al, 2018). Yet adaptation effects in point-light BM gender recognition indicate that this process is rather unlikely to be based on extracting low-level perceptual features (Jordan et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…This outcome appears to dovetail with recent reports indicating that females and males tend to use different types of information during BM processing and gender recognition in point-light displays: females rely on form and motion cues together, whereas males use motion cues solely (Hiris et al, 2018). This is also in line with recent findings on gender recognition in human infants aged 4-18 months: in a habituation paradigm, boys more easily differentiate the gender of a pointlight walker, presumably possessing higher sensitivity to motion parameters (Murray et al, 2018;Tsang et al, 2018). Yet adaptation effects in point-light BM gender recognition indicate that this process is rather unlikely to be based on extracting low-level perceptual features (Jordan et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…We first analyze data aggregated across the familiarization and test phases of the three experiments to test for a male PLD preference (cf. Tsang, Ogren, et al, 2018). Next, we analyze for gender matching at test in each experiment, followed by analyses of relations between individual differences in F I G U R E 2 Female (left in this example) and male (right) PLDs were viewed as a female or male voice was heard (Experiments 1 and 2).…”
Section: Analysis Planmentioning
confidence: 99%
“…Recently, Tsang, Ogren, et al (2018) reported results from two experiments that shed light on infants' perception of gender in PLDs. In the first experiment, Tsang et al asked whether infants would show a preference for female (vs. male) PLDs, as they do for female (vs. male) faces (Quinn et al, 2002) and perhaps voices (Decasper & Prescott, 1984;Spence & Freeman, 1996; but see Werker & McLeod, 1989).…”
mentioning
confidence: 99%
See 2 more Smart Citations